Adapting Care Groups to Urban Slums: A Case Study of a Church-Based Effort to Improve Maternal and Child Health Outcomes in Mathare, Nairobi, Kenya - Judith Siambe Opiyo; Paul Shetler Fast (Health for All Nations, 2019)
Progress on maternal and child health has been slow and uneven in Africa, with widening geographic and socio-economic disparities despite economic growth and continued investments in health systems. In Kenya, modest national-level gains mask wide disparities in progress, with near stagnation among the very poor, those with the least education, and those living in either extremely rural contexts or dense informal urban slums. Progress toward Kenya's maternal and child health Sustainable Development Goals will depend on finding new ways to work effectively in dense urban slums where poverty and ill-health are increasingly concentrated. Effective approaches require addressing significant knowledge, behavior, and trust gaps, especially with the most vulnerable residents of slum communities like Nairobi's Mathare. Care groups were designed to address these gaps but have only been effectively tested and scaled in rural and peri-urban environments. The Center for Peacebuilding and Nationhood's Maternal and Child Health Care Group project supported by Mennonite Central Committee in Mathare, one of the largest informal settlements in Kenya, was one of the first to adapt the Care Group model to an urban slum. Adapting the model was necessary in this challenging context characterized by high population density, crowding, extremely transient and unstable populations, low social trust, lack of traditional social structures, high crime, political disruption, and frequent rapid onset disasters. This study shows the pilot's success and challenges in adapting care groups to the realities of a dense African urban slum, the innovative strategies the project has used, and the unique benefits of doing this work on a small scale rooted in a local church organization.